Geometric and Mechanical Modelling of Textiles - Sherburn, Martin (2007)
The quality of a composite material produced using a textile reinforcement depends largely on the way the textile deforms during processing. To ensure the production of high quality parts and minimise costs in designing such parts it is necessary to develop methods to predict the deformations of textiles.